Pengetahuan dan Praktik Konsumsi Jamu Jun pada Masyarakat Semarang - Muhammad Rizky Adi Pratama; Fauzan Azalfa Nurhuda (Universitas Padjadjaran, 2018)
Jamu jun is a traditional drink from Demak and is popular in along the north coast of Central Java. The ingredients of jamu jun are 12 natural herbs. One of jamu jun outlets is Semawis Market in the Chinatown area of Semarang City. Jamu jun can be classified as a beverage that has benefits because the ingredients used are natural and used to warm the body and to treat some minor ailments such as gastritis. This research discusses the knowledge and practice of consumption of jamu jun in the Semarang community by using a qualitative research design. The scarcity of jamu jun makes knowledge and practice of consumption of this herbal medicine needs to be discussed. The results of this research is both the seller and consumer of jamu jun in Semarang understand the ingredients, manufacturing process, and benefits of herbal medicine. The consumer also strongly believes in the efficacy of herbal medicine so they preserve the practice of consuming jamu jun.